2021
DOI: 10.1093/ecco-jcc/jjaa265
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Acute Severe Colitis—Controversies in Clinical Practice in 2021

Abstract: Acute severe ulcerative colitis (ASUC) remains a common medical emergency, with 25% of patients with ulcerative colitis experiencing at least one event in their disease course. Despite advances in medical therapy, ASUC continues to be associated with considerable morbidity and mortality, with up to 30% of patients requiring colectomy during initial admission. Our aim was to review the current controversies and recent progress in risk stratification, prediction of outcome, and personalisation of care in ASUC. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…These results indicated that vitexin may be a promising agent for colitis treatment. However, as compared to chronic colitis model, acute colitis model can not reflect the dynamic course of colitis development in patients . So, further investigation should be performed to explore the effect of vitexin on treating DSS-induced chronic ulcerative colitis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that vitexin may be a promising agent for colitis treatment. However, as compared to chronic colitis model, acute colitis model can not reflect the dynamic course of colitis development in patients . So, further investigation should be performed to explore the effect of vitexin on treating DSS-induced chronic ulcerative colitis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers and composite scoring systems might help predict outcomes in ASUC. However, the roles of individual biomarkers require further clarification and there remains considerable uncertainty over the utility and preferences of the scoring system [ 27 ]. An effective predictive tool could help physicians identify patients requiring escalation to reduce unnecessary steroid exposure and improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the model can be modified by adjusting the baseline hazard or model intercept to better suit the average outcome risk in a larger external population [ 35 ]. Second, endoscopic features and laboratory data are currently routinely involved in the diagnosis and decision-making of clinicians, which could introduce circularity of argument, an inevitable inherent issue in data interpretation, and a prospective study may help in the future [ 27 ]. Moreover, in addition to endoscopic features and laboratory data, many novel predictors for IVCS response in UC patients have been proposed, including fecal calprotectin levels [ 36 , 37 ] and histological indices [ 38–40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, by treating patients with a predicted severe disease more aggressively early on, the natural course of the disease might be changed thereby improving long-term outcome. This applies for both – newly diagnosed patients and for patients during the disease course in case of severe complications requiring hospitalization for urgent rescue therapy [ 17 ]. However, current data comparing generalized top-down (i.e.…”
Section: Existing Biomarkers In Ibdmentioning
confidence: 99%